Paxillin family members function as Csk-binding proteins that regulate Lyn activity in human and murine platelets - Rathore, Vipul B. (Portland Press Ltd., 2007)
SFKs (Src family kinases) contribute importantly to platelet function in haemostasis. SFK activity is controlled by Csk (C-terminal Src kinase), which phosphorylates a C-terminal tyrosine residue on SFKs, resulting in inhibition of SFK activity. Csk is recruited to sites of SFK activity by tyrosine-phosphorylated Csk-binding proteins. Paxillin, a multidomain adaptor protein, has been shown to act as a Csk-binding protein and to inhibit Src activity during growth factor signalling. Human platelets express Hic-5, a member of the paxillin family; however, its ability to act as a Csk-binding protein has not been characterized. We sought to identify and characterize the ability of paxillin family members to act as Csk-binding proteins during platelet activation. We found that murine and human platelets differ in the complement of paxillin family members expressed. Human platelets express Hic-5, whereas murine platelets express paxillin and leupaxin in addition to Hic-5. In aggregating human platelets, Hic-5 was tyrosine phosphorylated and recruited Csk via its SH2 domains. In aggregating murine platelets, however, Csk bound preferentially to paxillin, even though both paxillin and Hic-5 were abundantly present and became tyrosine phosphorylated. The SFK Lyn, but not Src or Fyn, was associated with paxillin family members in resting and aggregated human and murine platelets. Lyn, however, was phosphorylated on its C-terminal inhibitory tyrosine residue only following platelet aggregation, which was coincident with recruitment of Csk to paxillin and/or Hic-5 in a manner dependent on prior α(IIb)β(3) engagement. These observations support the notion that Hic-5 and paxillin function as negative feedback regulators of SFKs in aggregated platelets and that, when both are present, paxillin is preferentially used.